Educação tecnológica e pré-sal: necessidades e urgências - Maciel, Patricia de Souza (2011)
The purpose of this dissertation is whether the demand for manpower trained in technical school for the sector of Oil and Gas (O&G) is in balance with the offer of that training in the Brazilian education system. The methodology used to obtain such information was based on School Census 2000 and 2008 where data were worked out in order to clarify the numbers of enrollments in secondary technical level demanded by the sector of O&G. The demand for manpower with that qualification as a data source was the 2010-2014 Business Plan Program for Mobilization of the National Oil and Natural Gas (PROMINP). This Program identified the future demand for manpower for the Sector of the O&G until 2014 where the occupational categories are mapped prerequisite training and experience. In order to better understand the object of this study was dome a review of the literature with regard to technical education in Brazil but also the importance of the education to economic growth and the peculiarities of the oil economy in different countries possessors of those mines, or that is, developed and underdeveloped countries. Analysis showed that enrollment in technical education in Brazil had a significant increase between the dates 2000 and 2008. It also don´t bring balance with the characteristic of the dynamics of the productive sectors of the economy mainly due to heating of the economy before the global growth especially in the Construction Industry as well as in the Oil and Natural Gas Engineering and a Naval account of the discovery of oil in the Pre-Salt. Another important aspect is that one of the major problems of qualification of manpower in Brazil is due to a bad quality of the student´s school and high school which makes difficult a good performance in office work and also this ability to learn new functions. The rapprochement between the supply of the education system and the demand for manpower with training mid-level technical support for the sector O&G showed that most technical courses demanded or had no enrollment in 2008, had few enrollment in 15 states with demand expect to occur and those enrollment were unevenly distributed among states. The analysis therefore signalize the needed of a public policy that enables the adequacy of the education system (Secondary Technical Education) to Sector of O&G in terms of enrollment and its distribution between the oil producing states and in relation to technical expertise offered